Chronic kidney disease in the context of multimorbidity patterns: the role of physical performance: The screening for CKD among older people across Europe (SCOPE) study - Corsonello, Andrea (BMC Geriatr, 2020)
BACKGROUND: Chronic kidney disease (CKD) is known to be associated with several co-occurring conditions. We aimed at exploring multimorbidity patterns associated with CKD, as well as the impact of physical performance and CKD severity on them in a population of older outpatients. METHODS: Our series consisted of 2252 patients enrolled in the Screening of CKD among Older People across Europe multicenter observational study. Hypertension, stroke, transient ischemic attack, cancer, hip fracture, osteoporosis, Parkinson’s disease, asthma, chronic obstructive pulmonary disease, congestive heart failure, angina, myocardial infarction, atrial fibrillation, anemia, CKD (defined as GFR < 60, < 45 or < 30 ml/min/1.73 m(2)), cognitive impairment, depression, hearing impairment and vision impairment were included in the analyses. Physical performance was assessed by the Short Physical Performance Battery (SPPB) and used as stratification variable. Pairs of co-occurring diseases were analyzed by logistic regression. Patterns of multimorbidity were investigated by hierarchical cluster analysis. RESULTS: CKD was among the most frequently observed conditions and it was rarely observed without any other co-occurring disease. CKD was significantly associated with hypertension, anemia, heart failure, atrial fibrillation, myocardial infarction and hip fracture. When stratifying by SPPB, CKD was also significantly associated with vision impairment in SPPB = 5–8 group, and hearing impairment in SPPB = 0–4 group. Cluster analysis individuated two main clusters, one including CKD, hypertension and sensory impairments, and the second including all other conditions. Stratifying by SPPB, CKD contribute to a cluster including diabetes, anemia, osteoporosis, hypertension and sensory impairments in the SPPB = 0–4 group. When defining CKD as eGFR< 45 or 30 ml/min/1.73 m(2), the strength of the association of CKD with hypertension, sensory impairments, osteoporosis, anemia and CHF increased together with CKD severity in pairs analysis. Severe CKD (eGFR< 30 ml/min/1.73 m(2)) contributed to a wide cluster including cardiovascular, respiratory and neurologic diseases, as well as osteoporosis, hip fracture and cancer. CONCLUSIONS: CKD and its severity may contribute significantly to specific multimorbidity patterns, at least based on the cluster analysis. Physical performance as assessed by SPPB may be associated with not negligible changes in both co-occurring pairs and multimorbidity clusters. TRIAL REGISTRATION: The SCOPE study is registered at clinicaltrials.gov (NCT02691546).